2016
DOI: 10.1186/s12887-016-0544-7
|View full text |Cite
|
Sign up to set email alerts
|

Perceived barriers and facilitators to participation in physical activity for children with disability: a qualitative study

Abstract: BackgroundChildren with disability engage in less physical activity compared to their typically developing peers. Our aim was to explore the barriers and facilitators to participation in physical activity for this group.MethodsTen focus groups, involving 63 participants (23 children with disability, 20 parents of children with disability and 20 sport and recreation staff), were held to explore factors perceived as barriers and facilitators to participation in physical activity by children with disability. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
223
1
28

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 243 publications
(265 citation statements)
references
References 28 publications
13
223
1
28
Order By: Relevance
“…Previous publications have shown that certain central factors related to the environment and PA characteristics are decisive for facilitating PA adherence among individuals with impairments (Shields & Synnot, 2016;Stuart et al, 2006). One important environmental factor is the instructor, who has the main responsibility for involving all participants in activities and making those activities safe, educational and enjoyable for them.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous publications have shown that certain central factors related to the environment and PA characteristics are decisive for facilitating PA adherence among individuals with impairments (Shields & Synnot, 2016;Stuart et al, 2006). One important environmental factor is the instructor, who has the main responsibility for involving all participants in activities and making those activities safe, educational and enjoyable for them.…”
Section: Discussionmentioning
confidence: 99%
“…One perspective is to explore the individuals' experiences. Some studies have assessed the self-perceived facilitators of and barriers to PA participation among children and adolescents with various physical disabilities (Shields & Synnot, 2016) and visual impairments (Greguol, Gobbi, & Carraro, 2015;Haegele & Porretta, 2015;Lieberman, Robinson, & Rollheiser, 2006;Stuart, Lieberman, & Hand, 2006;Wiskochil, Lieberman, Houston-Wilson, & Petersen, 2007). Reported facilitators include family involvement, PA being highly valued by individuals, socialization, fun and a sense of success, the competence of the instructor, autonomy in the choice of activities and peer acceptance (Shields & Synnot, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…O apoio emocional da família, dos amigos e profissionais foi apontado como facilitador de uma maior participação em atividades de lazer das pessoas com deficiência [27][28][29] . A sociedade tem que promover uma abordagem inclusiva para programas comunitários e serviços que reconheçam e apoiem as necessidades de pessoas com deficiência [23][24][25][26][27][28][29][30] . Embora normalmente haja uma necessidade de serviços de AF separados ou adaptados, o fato de que esses programas são pouco oferecidos na maioria das comunidades em todo o mundo, especialmente nos países mais pobres, onde os recursos dedicados ao cuidado e bem-estar são limitados, há a necessidade de maior número de programas inclusivos de AF que forneçam elementos de adaptação para as pessoas com deficiência 8 .…”
Section: Discussionunclassified